Efficacy of fructooligosaccharide versus placebo for treatment of acute diarrhea in children: A double-blind randomized clinical trial - Reni Suryanty; Supriatmo Supriatmo; Berlian Hasibuan; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2005)
Objective To compare the efficacy of fructooligosaccharide (FOS)versus placebo in pediatric patients with acute diarrhea with re-gard to duration and frequency of diarrhea and the volume andconsistency of the stools.Methods This double-blind randomized clinical trial was carriedout from July to November 2003 in the pediatric intensive careunit, outpatient clinic, and pediatric ward of Adam Malik Hospitaland Pirngadi Hospital, Medan. Subjects were children and infantsaged 4 to 24 months suffering from acute diarrhea without dehy-dration or with mild to moderate dehydration whose parents gaveconsent. Children included in this trial received tablets of either600 mg FOS or 761 mg fructulin as placebo. Patients with mild tomoderate dehydration were initially rehydrated according to theWHO protocol. Afterwards, 10 tablets of FOS or placebo were givento each subject to be taken twice daily. In subjects without dehy-dration, the tablets were given by their parents. Daily follow-upwas performed, in which body weight, temperature, duration andfrequency of diarrhea, and the volume and consistency of stoolswere recorded. For outpatients, home visits were made.Results Out of 142 children who met inclusion criteria, 135 com-pleted the study. These consisted of 68 children in the FOS groupand 67 in the placebo group. Subjects were mostly <12 months ofage (57.0%), male (57.8%), and moderately malnourished (34.1%).There was no statistically significant difference between both groupsin the duration and frequency of diarrhea and the volume and con-sistency of stools (P>0.05).Conclusion There is no effect of the administration of FOS assupplemental therapy on the duration and frequency of diarrheaand on the volume and consistency of stools in children with acutediarrhea